Morphomechanics and developmental constraints in the evolution of ammonites shell form - Erlich, A; Moulton, D; Goriely, A; Chirat, R (Wiley, 2016)
The idea that physical processes involved in biological development underlie morphogenetic rules and channel morphological evolution has been central to the rise of Evolutionary Developmental Biology (Evo-Devo). Here we explore this idea in the context of seashell morphogenesis. We show that a morphomechanical model can predict the effects of variations in shell shape on the ornamental pattern in ammonites, a now extinct group of cephalopods with external chambered shell. Our model shows that several seemingly unrelated characteristics of synchronous, ontogenetic, intraspecific and evolutionary variations in ornamental patterns among various ammonite species may all be understood from the fact that the mechanical forces underlying the oscillatory behaviour of the shell secreting system scale with the cross-sectional curvature of the shell aperture. This simple morphogenetic rule, emerging from biophysical interactions during shell formation, introduced a non-random component in the production of phenotypic variation and influenced the morphological evolution of ammonites over millions of years. As such, it provides a paradigm for the concept of “developmental constraints”.